2017
DOI: 10.1096/fj.201601320r
|View full text |Cite
|
Sign up to set email alerts
|

Excess centrosomes induce p53‐dependent senescence without DNA damage in endothelial cells

Abstract: Tumor blood vessels support tumor growth and progression. Centrosomes are microtubule organization centers in cells, and often up to 30% of tumor endothelial cells (ECs) acquire excess (>2) centrosomes. Although excess centrosomes can lead to aneuploidy and chromosome instability in tumor cells, how untransformed ECs respond to excess centrosomes is poorly understood. We found that the frequency of primary human ECs with excess centrosomes was quickly reduced in a p53-dependent manner. Excess centrosomes in EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…2B ). The results suggested that the activation of the P53/P21 pathway, mediated by the DNA damage response, could underlay the senescence of A375 cells as reported 14 , 15 .…”
Section: Resultsmentioning
confidence: 76%
“…2B ). The results suggested that the activation of the P53/P21 pathway, mediated by the DNA damage response, could underlay the senescence of A375 cells as reported 14 , 15 .…”
Section: Resultsmentioning
confidence: 76%
“…All cells were maintained at 37 °C and 5% CO 2 . Tetracycline-inducible Plk4 overexpression HUVEC were generated as previously described [13,17,25]. Viruses were produced by the UNC Lenti-shRNA Core Facility.…”
Section: Cell Culturementioning
confidence: 99%
“…BrdU incorporation was an adaptation (Yu et al, 2017). Briefly, HUVEC were incubated with 10 µM BrdU (Millipore Sigma, #B5002) in flow media for the last 90 min of flow and fixed in ice-cold 100% methanol.…”
Section: Immunofluorescencementioning
confidence: 99%